Standardized continuing teacher training: an analysis of the SEED-Paraná project - Tozetto, Susana Soares [UNESP]; de Góis Domingues, Thaiane (Universidade Estadual de Ponta Grossa (UEPG), 2023)
This research has as its object of study the continuing education project of the State Secretariat for Education and Sport of Paraná (SEED-PR). Its objective is to list the characteristics of the training projects made available on the Secretariat's website and to establish relationships between training and the (im)possibilities of development and teacher appreciation. The documentary research was conducted on the website of the public education network in Paraná in 2022. It is concluded that the materials and content made available materialize the standardization of teacher training through digital platforms and strategies of training content in Paraná. The evidence triggers the precariousness of continuing training and its disconnection with professional development and teacher appreciation. Although continuing training is part of professional development, when it assumes a standard and transmissive perspective, the connotation that is given to the teaching training process distances itself from the possibility of study and reflection on the part of teachers.
La formación continua estandarizada del profesor: un análisis del Proyecto de la SEED-Paraná
A formação continuada padronizada do professor: uma análise do Projeto da SEED-Paraná
Keywords: Continuing training; Teachers' education policies; Valorization of teaching